IMPLEMENTASI METODE JIGSAW DALAM MENINGKATKAN KETRAMPILAN KOMUNIKASI LISAN SISWA SMALB MATA PELAJARAN PAI DI SLB NEGERI TULUNGAGUNG - Dafid Fajar Hidayat. HS (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2024)
Basically, every human being cannot be separated from interacting with other humans. As social creatures, humans always try to build relationships with others. However, some people are limited in communication (have special needs), as we know, students at Special Schools (B-Deaf) are limited in one of their senses, namely hearing, which causes communication to be less than fluent. Student deafness concerns individual hearing conditions, namely the student's inability to perceive verbal communication or other sounds that are adjusted to a certain frequency and intensity. By implementing the jigsaw method in PAI learning, it is hoped that it will be able to provide solutions in oral communication skills. The aim of this research is to find out how the implementation of the jigsaw method improves the oral communication skills of SMALB Tulungagung students. This research uses a qualitative method with a descriptive type. Descriptive research type is used as a procedure to propose problem solving by highlighting the state of the object being studied. Data collection took place from 01 August to 15 October 2023 at the Tulungagung State Special School. The results of the research showed that there was an increase in the oral communication skills of Tulungagung State High School students through the implementation of the jigsaw method in PAI subjects. The weakness of this research is that it does not cover all subjects so this research cannot yet be generalized and needs to be studied by further researchers